A nationwide study of level of job satisfaction of nursing personnel in Iran - Z Monjamed; T Ghorbani; F Mostofian; R Oveissipour; S Nakhost Pandi; M Mahmoudi (Tehran University of Medical Sciences, 2005)
Introduction: Level of job satisfaction reflects positive or negative attitude of person toward his/her job and is influenced by many factors. Job satisfaction of nursing personnel directly affects their quality of care. Attention to this issue means attention to community health. Materials and Methods: This study is a descriptive, cross sectional research, conducted to identify the level of job satisfaction of nursing personnel of health, therapeutic and medical education centers of the entire country in the year 2001. Sample size was 4000 and nurses were selected through random stratified sampling method. Data collection tool was questionnaire of Herzberg job satisfaction which was sent by mail. Job satisfaction was classified into three levels: low (0-33.33%), moderate (33.34-66.67%) and high (66.68-100%). Results: We received back a total of 3029 questionnaires. Results showed that the majority of nurses had moderate level of job satisfaction in domains of working place situation (62.9%), relationship with colleagues (69.6%), professional situation (74.3%), supervision and administration (57.6%), managerial policies (50%) and personnel life in relation to the job (80.6%). Job satisfaction level was low in domains of job security (63.5%) and salary and benefits (77.3%). 2 test showed a significant relationship between age, job position, level of education, job experience, over time working, type of over time working, type of accommodation and participation in continuing education programs and job satisfaction. Conclusion: As a whole, the level of job satisfaction of majority of nursing personnel was moderate and the majority of subjects were not satisfied with welfare possibilities of their job. According to the research results it is recommended that the authorities try to increase the salary and financial benefits of nursing personnel and also to develop welfare possibilities of this class of community.